Decoupling the influence of systemic variables in the peripheral and cerebral haemodynamics during ECMO procedure by means of oblique and orthogonal subspace projections (2012)
Extra-Corporeal Membrane Oxygenation (ECMO) is a life support system for infants and children with cardio-respiratory failure. During ECMO it is possible to have unstable cerebral haemodynamics, due to strong oscillations in the systemic variables, among other factors, which may lead to brain damage in the patients. Therefore, monitoring the coupling between cerebral haemodynamics and systemic signals might alert us of possible imminent brain damage. In this study we explore the use of orthogonal and oblique subspace projections in the decoupling of these variables, by assessing the ratio between the projections of the haemodynamic variables, onto the subspace spanned by the systemic variables, and the original signals. The coupling of these two systems may differ as different protection mechanisms protect the peripheral system and the brain. Subspace projection was able to decompose the heamodynamic variables as a sum of components related to each systemic variable, separately. As expected, stronger coupling was found between the peripheral haemodynamic and the systemic variables.